CD34T+ Humanized Mouse Model to Study Mucosal HIV-1 Transmission and Prevention - Vanshylla, Kanika (Vaccines (Basel), 2021)
Humanized mice are critical for HIV-1 research, but humanized mice generated from cord blood are inefficient at mucosal HIV-1 transmission. Most mucosal HIV-1 transmission studies in mice require fetal tissue-engraftment, the use of which is highly restricted or prohibited. We present a fetal tissue-independent model called CD34T+ with enhanced human leukocyte levels in the blood and improved T cell homing to the gut-associated lymphoid tissue. CD34T+ mice are highly permissive to intra-rectal HIV-1 infection and also show normal env diversification in vivo despite high viral replication. Moreover, mucosal infection in CD34T+ mice can be prevented by infusion of broadly neutralizing antibodies. CD34T+ mice can be rapidly and easily generated using only cord blood cells and do not require any complicated surgical procedures for the humanization process. Therefore, CD34T+ mice provide a novel platform for mucosal HIV-1 transmission studies as well as rapid in vivo testing of novel prevention molecules against HIV-1.